O canto do bico do papagaio: a luta indígena Apinajé pela correção dos limites de sua terra no Estado do Tocantins - Braga, Luíza Ribeiro Sampaio (2025)
The traditional peoples known as the Apinajé make their territory their life's struggle. Having occupied the Tocantins Cerrado for over five centuries, the Apinajé indigenous peoples' lives were changed by the restriction of their permanent occupation territory as a direct consequence of the construction of the Trans-Amazonian highway. With the arrival of the pioneering front that came along with the highway, armed with property titles for these lands and with the endorsement of various state incentives aimed at the development of agribusiness, the squatters gradually began to occupy the indigenous territory historically occupied by the Apinajé people. The Apinajé peoples' concept of rights is shaped by their strong and intense relationship with the land, which has a cosmological and historical reference, used for hunting, fishing and gathering plants for ritual and medicinal purposes. Agribusiness, in turn, protects itself under the cloak of development and property secured by title. In this sense, this work seeks to understand, 35 (thirty-five) years after the promulgation of the Federal Constitution of 1988 – CRFB/88, which recognized their original right to the lands traditionally occupied, how these peoples still face several obstacles to the realization of this fundamental right, which is one of the central themes of their struggles today, without neglecting to analyze the right of rural landowners who will have to cede their lands for demarcation in order to do justice to the categories involved. As the main obstacle to the realization of the right to redefine the boundaries of the territory, this work focuses on a critical analysis of the conflicts of interest surrounding the Apinajé indigenous land, focusing on the inertia and/or omission of the Brazilian State in fulfilling its constitutional duty to demarcate it in its entirety, analyzing the collision of the right to demarcation of indigenous territory and the right to private property. It is concluded that the justification for the suppression of the integral Apinajé territory no longer exists, due to the deviation from the original layout, and that the original official documents ratify the recognition of this remaining territory, persevering the right and the fight for the demarcation of the “Apinajé II” area.